Travelling Abroad to Understand Australia: Glenn Murcutt's Look at the Architecture of José Antonio Coderch. Issue 1 (2nd January 2021) - López-Bahut, Emma
ABSTRACT: This paper analyses the impact on Glenn Murcutt's architecture of his 1973 meeting in Barcelona with José Antonio Coderch (1913–1984), one of the most internationally celebrated Spanish architects of the twentieth century. It uncovers details about their initial meeting and explores buildings designed by Coderch that Murcutt visited in person. The paper then analyses the impact of this meeting on Murcutt's architecture by comparing two houses: The Laurie Short House (Sydney, 1974), designed immediately before the 1973 trip and finished upon Murcutt's return to Australia, and the Marie Short House (Kempsey, 1975). The study of Coderch's work transformed Murcutt in three basic ways: it facilitated his shift away from the archetypal glass pavilion, it spurred Murcutt's development of continuous interior/exterior spaces and it taught him to exploit vertical sun-shading devices and various shutter configurations that are characteristic of both traditional Mediterranean architecture and Coderch's work. From Coderch, Murcutt learned to connect contemporary architecture with the tradition of the place, both physically and symbolically. Meeting Coderch, and visiting his works in person, became a turning point in Murcutt's career and it reveals crucial links between Spanish and Australian architecture.